Calcium ion removal at different sodium chloride concentrations by free and immobilized halophilic bacteria. (1st February 2023) - Yan, Huaxiao; Cao, Jiahao; Teng, Minhan; Meng, Long; Zhao, Lanmei; Chi, Xiangqun; Han, Zuozhen; Tucker, Maurice E.; Zhao, Hui
Highlights: V. massiliensis increased pH to 9.1 under the action of NH3 and CA in HW. Ca 2+ ion precipitation ratios reached 87%−98% in immobilized bacterial groups. Immobilized bacteria decrease the inhibition effect of NaCl on Ca 2+ ion removal. Humic acid-like substances, protein, DNA and polysacharide promoted Ca 2+ removal. 3 biomineralization pathes were studied besides recycled and precultured bacteria. Abstract: Much attention has been paid to Ca 2+ ion removal by biomineralization due to the dangers of Ca 2+ on industrial processes and human health. However, Ca 2+ removal from hypersaline water by biomineralization is quite difficult due to there being few halophilic bacteria tolerating higher salinities. In this study, free and immobilized Virgibacillus massiliensis C halophilic bacteria exhibiting carbonic anhydrase activity were used to remove Ca 2+ ions from water at different NaCl concentrations. With increasing NaCl concentrations (10, 50, 100, 150 and 200 g/L), Ca 2+ ion concentrations in the presence of free bacteria and in two groups of immobilized bacteria for a period of 6 days sharply decreased from 1200 mg/L to 219–562 mg/L, 71–214 mg/L and 21–159 mg/L, respectively; Ca 2+ precipitation ratios were 55%-81%, 82%-94% and 87%-98%, respectively. The humic acid-like substances, protein, DNA and polysaccharide, released by the bacteria, promoted the Ca 2+ ion removal. The immobilized bacteria were able to be recycled and precultured, which would save industry costs and increase Ca 2+ ion removal efficiency. Biological processes for Ca 2+ ion removal include cell surface, intracellular and extracellular biomineralization. The biogenesis of calcium carbonate was proved by SEM-EDS, FTIR, XPS and stable carbon isotope values. This study provides insights into the effective removal of Ca 2+ ions by biomineralization in hypersaline water. Graphical abstract: Image, graphical abstract